INDIVIDUAL LANGUAGE LEARNERS IN AN EFL CLASSROOM: Some Differences - Narovana Andriamiarana; Gin Gin Gustine; Nenden Sri Lengkanawati (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2026)
In the field of education, we do not only concentrate on the knowledge we will deliver, but also consider those who will receive it. Learners play a crucial role in the teaching and learning process because they are integral to it. Learners can differ in psychological, social, and environmental aspects, as well as in their culture and background. However, these differences impact learners’ performance in class, as they will develop at different rates, affecting the achievement of the learning objectives. Investigating EFL learners is essential because their diverse psychological, cognitive, environmental, and cultural differences strongly influence classroom dynamics and teaching effectiveness, making it crucial to understand how these variations shape learning outcomes. This research aims to discover suitable teaching strategies to face the differences among individuals and to know the impacts of those differences in an EFL (English as a Foreign Language) classroom. To address the issues, we have used a qualitative research method through questionnaires with participants from Madagascar and Indonesia. The result of the study has shown us that learners’ differences have both positive and negative feedback. To face those, better to use different approaches such as the genre-based approach, differentiated instruction, and good teaching scaffolding.